Improved Syntheses of Benzyl Hydraphile Synthetic Cation-Conducting Channels - Curvey, Nichole S.; Luderer, Sarah E.; Walker, John K.; Gokel, George W. (Synthesis, 2014)
The tris(macrocycle)s that function in bilayer membranes as ion channels have recently shown versatile new applications such as antibiotic synergists and as agents for direct injection chemotherapy. This report records the development of new and versatile approaches to these molecules that produce significantly better overall yields for a group of previously reported hydraphiles having spacer chains ranging from octylene to hexadecylene.
Keywords: acylation; benzylation; macrocycles; reduction; supramolecular chemistry